Research of Green Supervision and Service Project System Based on the Cloud Service - Qiuhong Ye; Jiangbo Zou (Dianxin kexue)
The construction of network infrastructure plays a key role in the expansion of the telecommunications business，but its infrastructure projects lack uniform standards and effective protection of the environment in the process of planning，implementation，evaluation and management，resulting in a waste of resources，inefficiency， environmental pollution and other problems in the implementing process of the projects. Therefore，depending on the problems encountered in the project management of the telecommunications industry，a green project super vision thought combined with the cloud computing concept and smart mobile devices was introduced. An in-depth research of the construction of a project supervision services system based on the distributed architecture of cloud service was conducted. The purpose was to achieve the unified platform of projects，technical standardization，rea1-time supervision，management process integration，environmental protection and other effects.